Faith-Based Organizations’ Support of Veteran Congregants at Risk for Mental Health Conditions and Suicide: A Qualitative Study of Clergy Experiences in Los Angeles County - Santiago, Susana (Journal of religion and health, 2023)
Faith-based organizations (FBOs) are often "gatekeepers" to mental health care for congregants at risk of mental illness and suicide, especially U.S. military Veterans, but data to inform better collaboration are needed. We conducted focus groups with clergy in Los Angeles County to understand the mental health support FBOs provide and barriers to collaboration with the mental healthcare system. Clergy detailed strategies used to support the mental health of Veteran congregants. Barriers included stigma, limits in clergy training, and incomplete knowledge about community and VA mental health resources. Results suggest strategies to improve collaboration between FBOs and the mental healthcare system in Los Angeles County.